Mixed twitch and tetanus electrical stimulation via belt-electrode effectively attenuates denervation-induced muscle atrophy - Hiroyuki Uno; Mako Isemura; Shohei Kamiya; Ryuji Akimoto; Katsu Hosoki; Shunta Tadano; Karina Kouzaki; Yuki Tamura; Takaya Kotani; Koichi Nakazato (PLoS ONE, 2025)
Belt electrode skeletal muscle stimulation (B-SES) is a method of applying electricity to contract muscles using belt-shaped electrodes. We previously reported that twitch contractions increase mitochondrial synthesis and suppress muscle proteolysis. In contrast, tetanus contraction increases muscle protein synthesis and suppresses muscle proteolysis. This study aimed to determine whether combining twitch- and tetanus-mode stimulations, which are known to differentially regulate mitochondrial and protein synthesis pathways, can more effectively attenuate muscle atrophy induced by denervation. Male Sprague-Dawley rats were subjected to acute or chronic B-SES. In the acute study, animals were assigned to control (CONT), tetanus (60 Hz), or Combined Stimulation (CS: 7–8 Hz for 15 min to 60 Hz for 3 min) groups. Four groups were tested in the chronic study: CONT, denervation (DEN), DEN + 60 Hz, and DEN + CS groups. Acute stimulation resulted in significantly lower muscle glycogen level, increased phosphorylated AMPK and p70S6K in the gastrocnemius muscle (GAS、n = 4) at 60 and CS compared to CONT, with no difference between 60 and CONT. After seven days, both muscle wet weight and cross-sectional area (CSA) were significantly reduced in the DEN group. Although both 60 Hz and CS attenuated atrophy, CS resulted in greater preservation (GAS CSA: DEN + CS, 71% CONT; DEN + 60, 61% CONT). In conclusion, the combination of different stimulation modalities (frequencies) was more effective than continuous tetanus stimulation in preventing denervation-induced muscle atrophy owing to an increase in muscle protein synthesis and inhibition of mitochondrial reduction.